2019
DOI: 10.1108/rpj-09-2018-0249
|View full text |Cite
|
Sign up to set email alerts
|

The effect of process parameters on the residual stress of selective laser melted Inconel 718 thin-walled part

Abstract: Purpose High residual stress caused by the high temperature gradient brings undesired effects such as shrinkage and cracking in selective laser melting (SLM). The purpose of this study is to predict the residual stress distribution and the effect of process parameters on the residual stress of selective laser melted (SLMed) Inconel 718 thin-walled part. Design/methodology/approach A three-dimensional (3D) indirect sequentially coupled thermal–mechanical finite element model was developed to predict the resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…For the Y-component of stress, as shown in Figure 18(b1)–18(b4), the residual stress of whole the part is small, which is due to the small size in part width and the small temperature gradient perpendicular to the scanning direction (Chen et al , 2019b; Luo et al , 2018). Similar to the X-component of stress, the residual stress at the interface between the part and the substrate is high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Y-component of stress, as shown in Figure 18(b1)–18(b4), the residual stress of whole the part is small, which is due to the small size in part width and the small temperature gradient perpendicular to the scanning direction (Chen et al , 2019b; Luo et al , 2018). Similar to the X-component of stress, the residual stress at the interface between the part and the substrate is high.…”
Section: Resultsmentioning
confidence: 99%
“…However, the other researchers stated that increasing the laser power led to a reduction in the cooling rate and the high scanning speed caused a low energy density, which both brought low residual stress. Also, a high powder thickness induced a low residual stress due to the decreased energy input (Chen et al , 2019b). The influence of the process parameters was therefore complex because of the differences in material properties and processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results demonstrated that the consolidated parts' porosity significantly affects the temperature profile during the process. Another effect caused by the high-temperature gradients in the SLM process is the high residual stress (Chen et al, 2019a), which brings undesired consequences such as shrinkage and cracking during service (Chen et al, 2019b).…”
Section: Feedstock Materials Used In the Selective Laser Melting Processmentioning
confidence: 99%
“…Consequently, precise simulation of stress profiles of SLM elements is critical to understand the process for creating highquality components. Several numerical approaches have been established in recent years by various researchers to understand SLM process-induced behaviors, especially residual stresses, such as Bian et al(2019Bian et al( , 2020, Chen et al(2019aChen et al( , 2019b and Liu et al(2020b). To deal with the temperature distribution inside the material during the SLM processing, some early models incorporated finite element analysis (Khan et al, 2018a(Khan et al, , 2018bLi et al, 2017;Li and Xiong, 2019;Majeed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%